Biotechnology - Ekinci, Deniz (IntechOpen, 2015)
Over the recent years, biotechnology has become responsible for explaining interactions of biological tools and processes so that many scientists in the life sciences from agronomy to medicine are engaged in biotechnological research. This book contains an overview focusing on the research area of molecular biology, molecular aspects of biotechnology, synthetic biology and agricultural applications in relevant approaches. The book deals with basic issues and some of the recent developments in biotechnological applications. Particular emphasis is devoted to both theoretical and experimental aspect of modern biotechnology. The primary target audience for the book includes students, researchers, biologists, chemists, chemical engineers and professionals who are interested in associated areas. The book is written by international scientists with expertise in chemistry, protein biochemistry, enzymology, molecular biology and genetics, many of which are active in biochemical and biomedical research. We hope that the book will enhance the knowledge of scientists in the complexities of some biotechnological approaches; it will stimulate both professionals and students to dedicate part of their future research in understanding relevant mechanisms and applications.